Genotype and phenotype of WWOX gene related developmental and epileptic encephalopathy - Wang, T (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2024)
Objective: To summarize the genotype and clinical phenotype of children with WWOX gene related developmental and epileptic encephalopathy (DEE). Methods: Case series studies. The clinical data of 12 children with WWOX gene related DEE who were admitted to the Neurological Department of Children's Medical Center, Peking University First Hospital from June 2019 to December 2023 were analyzed. The children's characteristics of gene variation, clinical phenotype, auxiliary examination results, treatment and prognosis were analyzed. Results: Among 12 children with WWOX gene related DEE, there were 7 boys and 5 girls, the age of seizure onset ranged from 10 days to 6 months (median 1.8 months). Multiple seizure types were observed, including focal seizures in 10 cases, epileptic spasms in 9 cases, tonic seizures in 4 cases, myoclonic seizures in 1 case. Among 12 cases, 9 cases had multiple seizure types. All 12 cases showed microcephaly and global developmental delay. Video electroencephalography showed slowed background activity in 6 cases, hyperarrhythmia in 6 cases, multifocal discharges in 6 cases, and focal discharges in 1 case. Epileptic spasms were detected in 8 cases, tonic seizures in 4 cases and myoclonic seizures in 1 case. Brain magnetic resonance imaging showed bilateral frontotemporal subarachnoid space widening in 5 cases, deep sulci in 3 cases, bilateral ventricular enlargement in 2 cases, callosal hypoplasia in 5 cases, and delayed white matter myelination in 3 cases. The phenotypes of 12 cases were consistent with the diagnosis of DEE, and 8 of them were diagnosed with infantile epileptic spasm syndrome. All the WWOX gene variants in 12 cases were complex heterozygous variants, including 20 variants, 11 variants and 1 large intragenic WWOX gene deletion (p.Ala149Thr, p.Arg156Ser, p.R167Tfs*8, p.Leu186Val, c.605+5G>A, p.Trp218*, p.His263Arg, p.Leu275fs*19*1, p.N285Kfs*10, p.Ser304Tyr, p.Met326Arg, loss1 exon2-8) had not been reported previously. The age of last follow-up ranged from 11 months to 5 years and 3 months. During the follow-up, 1 case died at the age of 1 year and 10 months, 2 cases were seizure-free, and 9 cases still had seizures after multiple anti-seizure medications. Conclusions: The seizure onset age of children with WWOX gene related DEE is usually less than 6 months, and some of them in neonate. The common seizure types include focal seizures and epileptic spasms. Children usually have microcephaly and global developmental delay. WWOX gene related DEE usually has drug refractory epilepsy